Composite porous biological ceramic metal prosthesis and preparation method thereof
By using a combination technology of gradient porous structure and HA/β-TCP composite coating in metal prostheses, the problems of insufficient biological activity and limited bone integration capabilities of traditional metal prostheses are solved, and the balance and long-term stability of mechanical properties and biological activities are achieved.
Patent Information
- Application Number
- CN202411818321.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-11
AI Technical Summary
In long-term clinical applications, traditional metal prostheses face problems such as insufficient biological activity, limited bone integration ability and stress masking effect, and it is difficult to achieve long-term stability and bone tissue growth.
Selective laser melting (SLM) 3D printing technology was used to prepare Ti6Al4V alloy matrix with gradient porosity, and a combination of microarc oxidation pretreatment and electrophoretic deposition was used to form a HA/β-TCP composite coating on the porous metal surface, optimizing the heat treatment process to improve the crystallinity and mechanical properties of the coating.
The balance between mechanical properties and biological activity is achieved, the adhesion, proliferation and differentiation of bone cells is promoted, the long-term stability and bone integration ability of the implant are ensured, and the controllable degradation behavior and uniform coating distribution are provided.
Smart Images

Figure BDA0005182449800000151 
Figure BDA0005182449800000161 
Figure BDA0005182449800000162
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal prostheses, in particular to a metal prosthesis of composite porous bioceramics and a preparation method thereof. Background Art
[0002] With the rapid development of orthopedic medicine, orthopedic implants are playing an increasingly important role in the treatment of bone defects, joint replacement and other fields. However, traditional metal prostheses still face many challenges in long-term clinical applications, such as insufficient bioactivity, limited bone integration ability and stress shielding effect. These problems not only affect the long-term stability of the implant, but may also increase the risk of secondary surgery for patients, causing additional pain and financial burden to patients.
[0003] In recent years, researchers have been committed to developing new orthopedic implant materials to improve their biocompatibility and long-term stability. Among them, porous metal materials have attracted widespread attention due to their bone-like structure and good mechanical properties. However, simple porous metal structures still lack sufficient bioactivity and are difficult to effectively promote the growth and integration of bone tissue. On the other hand, bioceramic materials such as hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP) have been widely studied due to their excellent bioactivity and osteoconductivity, but their brittleness and poor mechanical properties limit their application in load-bearing parts.
[0004] In order to overcome the above problems, researchers have tried to combine porous metals with bioceramics in order to obtain composite materials with both mechanical properties and bioactivity. However, existing composite technologies still have some limitations. First, the design of porous structures often makes it difficult to take into account both mechanical properties and biocompatibility. Secondly, the bonding strength between the bioceramic coating and the metal substrate is insufficient and it is easy to fall off during use. Furthermore, the degradation rate of the bioceramic coating is difficult to control, which affects the long-term stability of the implant. Finally, the existing preparation process makes it difficult to form a uniform and dense bioceramic coating on the surface of a complex porous structure. Summary of the invention
[0005] The present invention aims at the above problems and proposes an innovative composite porous bioceramic metal prosthesis and its preparation method. The invention successfully solves many problems existing in the prior art through a carefully designed gradient porous structure, an optimized HA / β-TCP composite coating and an innovative preparation process.
[0006] The object of the present invention is to provide a composite porous bioceramic metal prosthesis, comprising:
[0007] A metal substrate, wherein the metal substrate is made of Ti6Al4V alloy, has a gradient porosity structure of 30-70%, and a pore size range of 200-600 μm;
[0008] The bioceramic coating is covered on the surface of the metal substrate and is composed of the following components in parts by weight:
[0009] Hydroxyapatite HA 60-80 parts;
[0010] β-tricalcium phosphate β-TCP 20-40 parts.
[0011] Preferably, the composition of the Ti6Al4V alloy comprises, by weight percentage:
[0012] Al5.5-6.5%, V3.5-4.5%, Fe≤0.25%, O≤0.13%, C≤0.08%, N≤0.05%, hydrogen H≤0.012%, and the balance is Ti, totaling 100%.
[0013] As a preference, the method comprises the following steps:
[0014] (1) Preparing porous Ti6Al4V matrix using selective laser melting (SLM) 3D printing technology;
[0015] (2) performing surface treatment on the porous Ti6Al4V substrate;
[0016] (3) Bioceramic coating on the surface treated porous Ti6Al4V substrate;
[0017] (4) Heat treatment of the coated samples.
[0018] Preferably, the process parameters of the SLM 3D printing in step (1) are:
[0019] Laser power is 150-250W, scanning speed is 600-1000mm / s, layer thickness is 30-50μm, spot diameter is 70-100μm, molding atmosphere is high-purity argon with purity ≥99.999%, molding chamber temperature is 80-120℃, and substrate preheating temperature is 150-200℃.
[0020] Preferably, the surface treatment in step (2) comprises the following sub-steps:
[0021] First, an acid etching treatment is performed, wherein the formula of the acid etching solution is HF (48 wt%): HNO3 (65 wt%): H2O = 1:4:5 (volume ratio), and the treatment is performed at 20-25° C. for 8-12 min, with a stirring speed of 200-300 rpm;
[0022] Secondly, alkali treatment is performed, wherein the alkali solution is 5-10 mol / L NaOH solution, and the treatment is performed at 60-80° C. for 4-6 hours with a stirring speed of 100-150 rpm;
[0023] Then, ultrasonic cleaning was performed with deionized water for 10-15 min at an ultrasonic frequency of 40-60 kHz;
[0024] Finally, dry at 60-80°C for 2-4h.
[0025] Preferably, the bioceramic coating in step (3) comprises the following sub-steps:
[0026] (a) MAO pretreatment by micro-arc oxidation;
[0027] (b) Electrophoretic deposition (EPD).
[0028] Preferably, the process parameters of the micro-arc oxidation MAO pretreatment are:
[0029] The electrolyte formula is Ca(CH3COO)2·H2O10-15g / L, Na2HPO4·12H2O20-30g / L, voltage is 300-400V, frequency is 500-1000Hz, duty cycle is 10-20%, processing time is 5-10min, and temperature is 10-20℃.
[0030] Preferably, the process parameters of the electrophoretic deposition (EPD) are:
[0031] The suspension formula is 6-8g / L HA powder, 2-4g / L β-TCP powder, 0.1-0.3g / L dispersant, and the solvent is ethanol;
[0032] The pH value is 4.0-5.0, the voltage is 60-80V, the deposition time is 3-5min, and the temperature is 20-25℃.
[0033] Preferably, the process parameters of the heat treatment in step (4) are:
[0034] The heating rate is 5-10°C / min, the heat treatment temperature is 800-1000°C, the holding time is 1-2h, and the furnace is used to cool to room temperature. The heat treatment atmosphere is high-purity argon with a purity of ≥99.999%.
[0035] Preferably, the preparation method of the HA powder and β-TCP powder comprises:
[0036] For HA powder, 23.6-24.0 g Ca(NO3)2·4H2O and 7.9-8.1 g (NH4)2HPO4 were dissolved in deionized water, and the (NH4)2HPO4 solution was slowly added to the Ca(NO3)2 solution under continuous stirring. The pH was adjusted to 10-11 with NH4OH, and the mixture was stirred at 70-80°C for 4-6 h. After aging for 24 h, the mixture was filtered, washed, and dried, and finally calcined at 900-1000°C for 2 h.
[0037] For β-TCP powder, 35.4-36.0 g Ca(NO3)2·4H2O and 15.8-16.2 g (NH4)2HPO4 were dissolved in deionized water, and the (NH4)2HPO4 solution was slowly added dropwise to the Ca(NO3)2 solution under continuous stirring, and the pH was adjusted to 7-8. The mixture was stirred at 80-90°C for 5-6 h, aged for 24 h, filtered, washed, and dried, and finally calcined at 900-1100°C for 3 h.
[0038] The obtained powder was ball-milled and then passed through a 200-mesh sieve.
[0039] The core innovation of the present invention is: first, a Ti6Al4V alloy matrix with gradient porosity is prepared by selective laser melting (SLM) 3D printing technology, achieving a balance between mechanical properties and biocompatibility. Secondly, a HA / β-TCP composite coating with strong bonding and uniform distribution is formed on the porous metal surface by combining micro-arc oxidation pretreatment and electrophoretic deposition. Furthermore, by precisely controlling the ratio of HA and β-TCP, the controllable regulation of the coating degradation rate is achieved. Finally, an optimized heat treatment process is used to further improve the crystallinity and mechanical properties of the coating.
[0040] From the perspective of materials science, the present invention cleverly utilizes the excellent mechanical properties and biocompatibility of Ti6Al4V alloy, while simulating the structural characteristics of natural bone tissue through the design of gradient porous structure. At the nanoscale, the synergistic effect of HA and β-TCP crystals creates a dynamically changing bioactive interface. The stable structure of HA provides a good attachment matrix for cells, while the moderate degradation of β-TCP continuously releases calcium and phosphorus ions, creating a microenvironment conducive to bone formation.
[0041] From the perspective of molecular structure and chemical mechanism, HA (Ca 10 (PO4)6(OH)2 and β-TCP (Ca3(PO4)2) are both calcium-phosphate compounds, but they differ in crystal structure and chemical properties. HA has a more stable hexagonal crystal structure, while β-TCP is an orthorhombic crystal. This structural difference leads to differences in their solubility and bioactivity in physiological environments. The hydroxyl group (OH-) of HA can interact with surrounding proteins and cells to improve biocompatibility. The higher solubility of β-TCP is conducive to the release of calcium and phosphorus ions and promotes the bone mineralization process.
[0042] From the perspective of atomic and molecular orbital theory, the titanium atoms in Ti6Al4V alloy have unfilled d orbitals, which enable it to form strong chemical bonds with oxygen atoms. During the micro-arc oxidation process, the TiO2 layer formed on the titanium surface not only enhances the adhesion of the coating, but also may further improve the biological activity through surface hydroxylation. At the same time, the semiconductor properties of TiO2 may affect the electron transfer process to a certain extent, thereby regulating the adhesion and proliferation behavior of cells.
[0043] The present invention achieves the following beneficial effects through the synergistic effect of multiple technical features:
[0044] 1. Optimized mechanical properties: The gradient porous structure not only reduces the overall stiffness and stress shielding effect, but also achieves uniform stress distribution through the gradual design of porosity.
[0045] 2. Enhanced bioactivity: HA / β-TCP composite coating provides an ideal bioactive surface, promoting the adhesion, proliferation and differentiation of bone cells. At the same time, the controlled degradation of the coating ensures continuous ion release and maintains a microenvironment conducive to bone formation for a long time.
[0046] 3. Improved bone integration ability: The porous structure provides an ideal space for bone tissue growth, while the bioceramic coating promotes the close integration of bone tissue and implants.
[0047] 4. Long-term stability: Through micro-arc oxidation pretreatment and optimized heat treatment process, the bonding strength between the coating and the substrate is significantly improved, ensuring the long-term stability of the implant.
[0048] 5. Adjustable degradation behavior: By precisely controlling the ratio of HA and β-TCP, the degradation rate of the coating can be precisely controlled to better match the reconstruction process of bone tissue.
[0049] 6. Uniform coating distribution: The innovative preparation process solves the problem of forming a uniform coating on the surface of complex porous structures, ensuring that the entire implant surface has ideal bioactivity.
[0050] 7. Bionic design: Multi-scale collaborative design, from nanoscale crystal structure to macroscopic gradient porous structure, better simulates the structural and functional characteristics of natural bone tissue.
[0051] In summary, the present invention has successfully developed a composite porous bioceramic metal prosthesis with excellent comprehensive performance through the integration and innovation of multidisciplinary knowledge. This prosthesis not only overcomes the limitations of traditional metal prostheses and bioceramic materials, but also achieves the optimization of mechanical properties, biological activity and long-term stability through multi-scale and multi-level collaborative design. The present invention provides new ideas and directions for the development of orthopedic implants, and is expected to bring significant improvements in clinical applications, provide better treatment effects for patients, reduce the risk of secondary surgery, and improve the quality of life. DETAILED DESCRIPTION
[0052] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0053] Example 1
[0054] This embodiment provides a composite porous bioceramic metal prosthesis and a preparation method thereof. The metal prosthesis includes a metal substrate made of Ti6Al4V alloy and a bioceramic coating covering the surface thereof. The metal substrate has a gradient porosity structure of 30% and a pore size of 200 μm. The bioceramic coating is composed of the following components in parts by weight: 80 parts of hydroxyapatite (HA) and 20 parts of β-tricalcium phosphate (β-TCP).
[0055] The components of the Ti6Al4V alloy include, by weight percentage, 5.5% aluminum (Al), 3.5% vanadium (V), 0.25% iron (Fe), 0.13% oxygen (O), 0.08% carbon (C), 0.05% nitrogen (N), 0.012% hydrogen (H), and the remainder is titanium (Ti), totaling 100%.
[0056] The preparation method of the composite porous bioceramic metal prosthesis comprises the following steps:
[0057] (1) The porous Ti6Al4V matrix was prepared by selective laser melting (SLM) 3D printing technology. The process parameters of SLM 3D printing were: laser power 150 W, scanning speed 600 mm / s, layer thickness 30 μm, spot diameter 70 μm, molding atmosphere was high-purity argon (purity 99.999%), molding chamber temperature 80 °C, and substrate preheating temperature 150 °C.
[0058] (2) Surface treatment is performed on the porous Ti6Al4V substrate. The surface treatment comprises the following sub-steps:
[0059] First, an acid etching treatment was performed, the formula of the acid etching solution was HF (48 wt%): HNO3 (65 wt%): H2O = 1:4:5 (volume ratio), and the treatment was carried out at 20°C for 8 min with a stirring speed of 200 rpm.
[0060] Secondly, alkali treatment was carried out, the alkali solution was 5 mol / L NaOH solution, the treatment was carried out at 60° C. for 4 h, and the stirring speed was 100 rpm.
[0061] Then, ultrasonic cleaning was performed with deionized water for 10 min at an ultrasonic frequency of 40 kHz.
[0062] Finally, it was dried at 60 °C for 2 h.
[0063] (3) Performing bioceramic coating on the surface treated porous Ti6Al4V substrate. The bioceramic coating includes the following sub-steps:
[0064] (a) Micro-arc oxidation (MAO) pretreatment: the electrolyte formula is Ca(CH3COO)2·H2O 10g / L, Na2HPO4·12H2O 20g / L, voltage 300V, frequency 500Hz, duty cycle 10%, treatment time 5min, temperature 10℃.
[0065] (b) Electrophoretic deposition (EPD): The suspension formula is 6 g / L HA powder, 2 g / L β-TCP powder, 0.1 g / L dispersant, and the solvent is ethanol; the pH value is 4.0, the voltage is 60 V, the deposition time is 3 min, and the temperature is 20 °C.
[0066] (4) The coated samples were heat treated. The process parameters of the heat treatment were: heating rate 5°C / min, heat treatment temperature 800°C, holding time 1h, furnace cooling to room temperature, and heat treatment atmosphere was high-purity argon (purity 99.999%).
[0067] In this embodiment, the preparation method of HA powder and β-TCP powder is as follows:
[0068] For HA powder, 23.6 g Ca(NO3)2·4H2O and 7.9 g (NH4)2HPO4 were dissolved in deionized water respectively, and the (NH4)2HPO4 solution was slowly added dropwise to the Ca(NO3)2 solution under continuous stirring. The pH was adjusted to 10 with NH4OH, and the reaction was stirred at 70°C for 4 h. After aging for 24 h, it was filtered, washed, dried, and finally calcined at 900°C for 2 h.
[0069] For β-TCP powder, 35.4 g Ca(NO3)2·4H2O and 15.8 g (NH4)2HPO4 were dissolved in deionized water respectively. The (NH4)2HPO4 solution was slowly added dropwise to the Ca(NO3)2 solution under continuous stirring. The pH was adjusted to 7. The reaction was stirred at 80°C for 5 h. After aging for 24 h, the mixture was filtered, washed, dried, and finally calcined at 900°C for 3 h.
[0070] The obtained powder was ball-milled and then passed through a 200-mesh sieve.
[0071] Example 2: Composite porous bioceramic metal prosthesis and preparation method thereof
[0072] This embodiment provides another composite porous bioceramic metal prosthesis and a preparation method thereof. The metal prosthesis includes a metal substrate made of Ti6Al4V alloy and a bioceramic coating covering the surface thereof. The metal substrate has a gradient porosity structure of 50% and a pore size of 400 μm. The bioceramic coating is composed of the following components in parts by weight: 70 parts of hydroxyapatite (HA) and 30 parts of β-tricalcium phosphate (β-TCP).
[0073] The components of the Ti6Al4V alloy include, by weight percentage, 6.0% aluminum (Al), 4.0% vanadium (V), 0.20% iron (Fe), 0.10% oxygen (O), 0.06% carbon (C), 0.03% nitrogen (N), 0.008% hydrogen (H), and the balance is titanium (Ti).
[0074] The preparation method of the composite porous bioceramic metal prosthesis comprises the following steps:
[0075] (1) The porous Ti6Al4V matrix was prepared by selective laser melting (SLM) 3D printing technology. The process parameters of SLM 3D printing were: laser power 200 W, scanning speed 800 mm / s, layer thickness 40 μm, spot diameter 85 μm, molding atmosphere was high-purity argon (purity 99.9995%), molding chamber temperature 100 °C, and substrate preheating temperature 175 °C.
[0076] (2) Surface treatment is performed on the porous Ti6Al4V substrate. The surface treatment comprises the following sub-steps:
[0077] First, an acid etching treatment was performed, the formula of the acid etching solution was HF (48 wt%): HNO3 (65 wt%): H2O = 1:4:5 (volume ratio), and the treatment was carried out at 22.5°C for 10 min with a stirring speed of 250 rpm.
[0078] Secondly, an alkali treatment was performed, the alkali solution was 7.5 mol / L NaOH solution, the treatment was performed at 70° C. for 5 h, and the stirring speed was 125 rpm.
[0079] Then, ultrasonic cleaning was performed with deionized water for 12.5 min at an ultrasonic frequency of 50 kHz.
[0080] Finally, it was dried at 70 °C for 3 h.
[0081] (3) Performing bioceramic coating on the surface treated porous Ti6Al4V substrate. The bioceramic coating includes the following sub-steps:
[0082] (a) Micro-arc oxidation (MAO) pretreatment: the electrolyte formula is Ca(CH3COO)2·H2O 12.5g / L, Na2HPO4·12H2O 25g / L, voltage 350V, frequency 750Hz, duty cycle 15%, treatment time 7.5min, temperature 15℃.
[0083] (b) Electrophoretic deposition (EPD): The suspension formula is HA powder 7 g / L, β-TCP powder 3 g / L, dispersant 0.2 g / L, and the solvent is ethanol; the pH value is 4.5, the voltage is 70 V, the deposition time is 4 min, and the temperature is 22.5 °C.
[0084] (4) The coated samples were heat treated. The process parameters of the heat treatment were: heating rate 7.5°C / min, heat treatment temperature 900°C, holding time 1.5h, furnace cooling to room temperature, and heat treatment atmosphere was high-purity argon (purity 99.9995%).
[0085] In this embodiment, the preparation method of HA powder and β-TCP powder is as follows:
[0086] For HA powder, 23.8 g Ca(NO3)2·4H2O and 8.0 g (NH4)2HPO4 were dissolved in deionized water respectively, and the (NH4)2HPO4 solution was slowly added dropwise to the Ca(NO3)2 solution under continuous stirring. The pH was adjusted to 10.5 with NH4OH, and the reaction was stirred at 75°C for 5 h. After aging for 24 h, it was filtered, washed, dried, and finally calcined at 950°C for 2 h.
[0087] For β-TCP powder, 35.7 g Ca(NO3)2·4H2O and 16.0 g (NH4)2HPO4 were dissolved in deionized water respectively, and the (NH4)2HPO4 solution was slowly added dropwise to the Ca(NO3)2 solution under continuous stirring. The pH was adjusted to 7.5, and the reaction was stirred at 85°C for 5.5 h. After aging for 24 h, it was filtered, washed, dried, and finally calcined at 1000°C for 3 h.
[0088] The obtained powder was ball-milled and then passed through a 200-mesh sieve.
[0089] Example 3
[0090] This embodiment provides a third composite porous bioceramic metal prosthesis and a preparation method thereof. The metal prosthesis includes a metal substrate made of Ti6Al4V alloy and a bioceramic coating covering the surface thereof. The metal substrate has a gradient porosity structure of 70% and a pore size of 600 μm. The bioceramic coating is composed of the following components in parts by weight: 60 parts of hydroxyapatite (HA) and 40 parts of β-tricalcium phosphate (β-TCP).
[0091] The components of the Ti6Al4V alloy include, by weight percentage, 6.5% aluminum (Al), 4.5% vanadium (V), 0.15% iron (Fe), 0.07% oxygen (O), 0.04% carbon (C), 0.02% nitrogen (N), 0.005% hydrogen (H), and the balance is titanium (Ti).
[0092] The preparation method of the composite porous bioceramic metal prosthesis comprises the following steps:
[0093] (1) The porous Ti6Al4V matrix was prepared by selective laser melting (SLM) 3D printing technology. The process parameters of SLM 3D printing were: laser power 250 W, scanning speed 1000 mm / s, layer thickness 50 μm, spot diameter 100 μm, molding atmosphere was high-purity argon (purity 99.9999%), molding chamber temperature 120 °C, and substrate preheating temperature 200 °C.
[0094] (2) Surface treatment is performed on the porous Ti6Al4V substrate. The surface treatment comprises the following sub-steps:
[0095] First, an acid etching treatment was performed, the formula of the acid etching solution was HF (48 wt %): HNO3 (65 wt %): H2O = 1:4:5 (volume ratio), and the treatment was carried out at 25°C for 12 min with a stirring speed of 300 rpm.
[0096] Secondly, alkali treatment was carried out, the alkali solution was 10 mol / L NaOH solution, the treatment was carried out at 80° C. for 6 h, and the stirring speed was 150 rpm.
[0097] Then, ultrasonic cleaning was performed with deionized water for 15 min at an ultrasonic frequency of 60 kHz.
[0098] Finally, it was dried at 80 °C for 4 h.
[0099] (3) Performing bioceramic coating on the surface treated porous Ti6Al4V substrate. The bioceramic coating includes the following sub-steps:
[0100] (a) Micro-arc oxidation (MAO) pretreatment: the electrolyte formula is Ca(CH3COO)2·H2O 15 g / L, Na2HPO4·12H2O 30 g / L, voltage 400 V, frequency 1000 Hz, duty cycle 20%, treatment time 10 min, temperature 20 °C.
[0101] (b) Electrophoretic deposition (EPD): The suspension formula is HA powder 8 g / L, β-TCP powder 4 g / L, dispersant 0.3 g / L, and the solvent is ethanol; the pH value is 5.0, the voltage is 80 V, the deposition time is 5 min, and the temperature is 25 °C.
[0102] (4) The coated samples were heat treated. The process parameters of the heat treatment were: heating rate 10°C / min, heat treatment temperature 1000°C, holding time 2h, furnace cooling to room temperature, and heat treatment atmosphere was high-purity argon (purity 99.9999%).
[0103] In this embodiment, the preparation method of HA powder and β-TCP powder is as follows:
[0104] For HA powder, 24.0 g Ca(NO3)2·4H2O and 8.1 g (NH4)2HPO4 were dissolved in deionized water respectively, and the (NH4)2HPO4 solution was slowly added dropwise to the Ca(NO3)2 solution under continuous stirring. The pH was adjusted to 11 with NH4OH, and the reaction was stirred at 80°C for 6 h. After aging for 24 h, the mixture was filtered, washed, dried, and finally calcined at 1000°C for 2 h.
[0105] For β-TCP powder, 36.0 g Ca(NO3)2·4H2O and 16.2 g (NH4)2HPO4 were dissolved in deionized water respectively, and the (NH4)2HPO4 solution was slowly added dropwise to the Ca(NO3)2 solution under continuous stirring. The pH was adjusted to 8, and the reaction was stirred at 90°C for 6 h. After aging for 24 h, it was filtered, washed, dried, and finally calcined at 1100°C for 3 h.
[0106] The obtained powder was ball-milled and then passed through a 200-mesh sieve.
[0107] Example 4
[0108] This embodiment provides a fourth composite porous bioceramic metal prosthesis and a preparation method thereof. The metal prosthesis includes a metal substrate made of Ti6Al4V alloy and a bioceramic coating covering the surface thereof. The metal substrate has a gradient porosity structure of 50% and a pore size of 400 μm. The bioceramic coating is composed of the following components in parts by weight: 65 parts of hydroxyapatite (HA) and 35 parts of β-tricalcium phosphate (β-TCP).
[0109] The components of the Ti6Al4V alloy include, by weight percentage, 6.0% aluminum (Al), 4.0% vanadium (V), 0.18% iron (Fe), 0.09% oxygen (O), 0.05% carbon (C), 0.03% nitrogen (N), 0.007% hydrogen (H), and the balance is titanium (Ti).
[0110] The preparation method of the composite porous bioceramic metal prosthesis comprises the following steps:
[0111] (1) The porous Ti6Al4V matrix was prepared by selective laser melting (SLM) 3D printing technology. The process parameters of SLM 3D printing were: laser power 200 W, scanning speed 800 mm / s, layer thickness 40 μm, spot diameter 85 μm, molding atmosphere was high-purity argon (purity 99.9997%), molding chamber temperature 100 °C, and substrate preheating temperature 175 °C.
[0112] (2) Surface treatment is performed on the porous Ti6Al4V substrate. The surface treatment comprises the following sub-steps:
[0113] First, an acid etching treatment was performed, the formula of the acid etching solution was HF (48 wt%): HNO3 (65 wt%): H2O = 1:4:5 (volume ratio), and the treatment was carried out at 22.5°C for 10 min with a stirring speed of 250 rpm.
[0114] Secondly, alkali treatment was carried out, the alkali solution was 7.5 mol / L NaOH solution, the treatment was carried out at 70° C. for 5 h, and the stirring speed was 125 rpm.
[0115] Then, ultrasonic cleaning was performed with deionized water for 12.5 min at an ultrasonic frequency of 50 kHz.
[0116] Finally, it was dried at 70 °C for 3 h.
[0117] (3) Performing bioceramic coating on the surface treated porous Ti6Al4V substrate. The bioceramic coating includes the following sub-steps:
[0118] (a) Micro-arc oxidation (MAO) pretreatment: the electrolyte formula is Ca(CH3COO)2·H2O 12.5g / L, Na2HPO4·12H2O 25g / L, voltage 350V, frequency 750Hz, duty cycle 15%, treatment time 7.5min, temperature 15℃.
[0119] (b) Electrophoretic deposition (EPD): The suspension formula is HA powder 7 g / L, β-TCP powder 3.5 g / L, dispersant 0.2 g / L, and the solvent is ethanol; the pH value is 4.5, the voltage is 70 V, the deposition time is 4 min, and the temperature is 22.5 °C.
[0120] (4) The coated samples were heat treated. The process parameters of the heat treatment were: heating rate 7.5°C / min, heat treatment temperature 900°C, holding time 1.5h, furnace cooling to room temperature, and heat treatment atmosphere was high-purity argon (purity 99.9997%).
[0121] In this embodiment, the preparation method of HA powder and β-TCP powder is as follows:
[0122] For HA powder, 23.8 g Ca(NO3)2·4H2O and 8.0 g (NH4)2HPO4 were dissolved in deionized water respectively, and the (NH4)2HPO4 solution was slowly added dropwise to the Ca(NO3)2 solution under continuous stirring. The pH was adjusted to 10.5 with NH4OH, and the reaction was stirred at 75°C for 5 h. After aging for 24 h, it was filtered, washed, dried, and finally calcined at 950°C for 2 h.
[0123] For β-TCP powder, 35.7 g Ca(NO3)2·4H2O and 16.0 g (NH4)2HPO4 were dissolved in deionized water respectively. The (NH4)2HPO4 solution was slowly added dropwise to the Ca(NO3)2 solution under continuous stirring. The pH was adjusted to 7.5. The reaction was stirred at 85°C for 5.5 h. After aging for 24 h, it was filtered, washed, dried, and finally calcined at 1000°C for 3 h.
[0124] The obtained powder was ball-milled and then passed through a 200-mesh sieve.
[0125] Through the above four embodiments, it can be seen that the composite porous bioceramic metal prosthesis of the present invention and the preparation method thereof have good controllability. By adjusting the gradient porosity and pore size of the Ti6Al4V alloy matrix, a balance between mechanical properties and biocompatibility can be achieved. By adjusting the ratio of HA and β-TCP in the bioceramic coating, the biological activity and degradation rate of the coating can be controlled. At the same time, the parameter adjustment of each step in the preparation method, such as SLM 3D printing, surface treatment, bioceramic coating and heat treatment, can have a significant impact on the performance of the final product.
[0126] It is worth noting that the present invention successfully forms a uniform bioceramic coating on the surface of a porous metal substrate by combining micro-arc oxidation pretreatment and electrophoretic deposition. This innovative coating method not only improves the bonding strength between the coating and the substrate, but also ensures the uniform distribution of the coating in the complex porous structure, thereby effectively improving the bioactivity and bone integration ability of the prosthesis.
[0127] In addition, by precisely controlling the preparation process of HA and β-TCP powders, the present invention ensures the high quality and repeatability of the bioceramic coating. This strict powder preparation process lays a solid foundation for the subsequent coating process and further ensures the performance stability of the final product.
[0128] In general, the composite porous bioceramic metal prosthesis and the preparation method thereof provided by the present invention, through the synergistic effect of multiple technical features, successfully solves the deficiencies of traditional metal prostheses in terms of biological activity, bone integration ability and long-term stability, and provides new ideas and directions for the development of orthopedic implants.
[0129] Comparative Example 1: Single Metal Matrix Prosthesis
[0130] This comparative example is intended to demonstrate the importance of a composite porous bioceramic coating. The prosthesis only contains a metal substrate made of Ti6Al4V alloy without a bioceramic coating. The metal substrate has a gradient porosity structure of 50% and a pore size of 400 μm.
[0131] The composition of the Ti6Al4V alloy is the same as that of Example 2. The preparation method only includes steps (1) and (2), and the specific parameters are consistent with those of Example 2. Due to the lack of a bioceramic coating, although the prosthesis has good mechanical properties, its bioactivity and bone integration ability are significantly lower than those of the composite prosthesis of the present invention. This highlights the key role of the bioceramic coating in improving the biocompatibility of the prosthesis.
[0132] Comparative Example 2: Non-gradient porosity structure prosthesis
[0133] This comparative example is intended to demonstrate the importance of gradient porosity structure. The prosthesis includes a Ti6Al4V alloy substrate and a bioceramic coating, but the metal substrate has a uniform 50% porosity structure with a pore size of 400 μm. The bioceramic coating components are the same as those in Example 2.
[0134] The preparation method is basically the same as that of Example 2, but in step (1), the SLM 3D printing parameters are adjusted to obtain a uniform porosity structure. The results show that although the prosthesis has certain biological activity, its stress distribution is not as uniform as that of the gradient structure, which may lead to stress shielding effect, thereby affecting the long-term stability and bone integration effect of the prosthesis.
[0135] Comparative Example 3: Single HA coating prosthesis
[0136] This comparative example is intended to demonstrate the synergistic effect of the HA and β-TCP composite coating. The metal substrate of the prosthesis is the same as that of Example 3, but the bioceramic coating is composed of only 100 parts of hydroxyapatite (HA).
[0137] The preparation method is basically the same as that of Example 3, but only HA powder is used in the electrophoretic deposition process of step (3). The results show that although HA has good biological activity, the degradation rate of a single HA coating is slow and cannot well match the reconstruction process of bone tissue. This proves the advantages of HA and β-TCP composite coating in regulating degradation rate and promoting bone integration.
[0138] Comparative Example 4: Prosthesis coated with high β-TCP content
[0139] This comparative example is intended to verify the optimal ratio range of HA and β-TCP. The metal substrate of the prosthesis is the same as that of Example 4, but the bioceramic coating composition is: 40 parts of HA and 60 parts of β-TCP.
[0140] The preparation method is basically the same as that of Example 4, except that the ratio of HA to β-TCP during electrophoretic deposition was adjusted. The results show that although an excessively high β-TCP content can accelerate the degradation rate of the coating, it may also lead to a decrease in the stability of the coating, which is not conducive to long-term bone integration. This verifies the rationality of the ratio range of HA to β-TCP in the present invention.
[0141] Comparative Example 5: Prosthesis without micro-arc oxidation pretreatment
[0142] This comparative example is intended to demonstrate the importance of micro-arc oxidation pretreatment. The basic composition of the prosthesis is the same as that of Example 1, but the micro-arc oxidation pretreatment step is omitted during the preparation process.
[0143] The preparation method is basically the same as that of Example 1, but the micro-arc oxidation pretreatment in step (3) is deleted, and electrophoretic deposition is directly performed. The results show that although the bioceramic coating can still be formed, the bonding strength between the coating and the metal substrate is significantly reduced, and the coating uniformity is poor. This proves the key role of micro-arc oxidation pretreatment in improving the adhesion and uniformity of the coating.
[0144] Comparative Example 6: Low-temperature heat treatment of prosthesis
[0145] This comparative example is intended to demonstrate the importance of heat treatment temperature. The basic composition of the prosthesis is the same as that of Example 4, but a lower temperature is used in the heat treatment step.
[0146] The preparation method is basically the same as that of Example 4, but in step (4), the heat treatment temperature is reduced to 700°C. The results show that although low-temperature heat treatment can improve the bonding strength between the coating and the substrate to a certain extent, it cannot fully stimulate the crystal phase transformation of the bioceramic, resulting in the biological activity and mechanical properties of the coating being inferior to the optimal range of the present invention. This verifies the rationality of the heat treatment temperature range in the present invention.
[0147] Through the above 6 comparative examples, it can be clearly seen that the invention has the following innovations and advantages in many aspects:
[0148] 1. The design of the composite porous structure effectively balances the mechanical properties and biocompatibility of the prosthesis.
[0149] 2. The gradient porosity structure optimizes stress distribution and reduces stress shielding effect.
[0150] 3. The composite coating of HA and β-TCP achieves synergistic regulation of bioactivity and degradation rate.
[0151] 4. Micro-arc oxidation pretreatment significantly improves the adhesion and uniformity of the coating.
[0152] 5. The optimized heat treatment process ensures high crystallinity and good mechanical properties of the coating.
[0153] The synergistic effect of these innovative features makes the composite porous bioceramic metal prosthesis of the present invention have significant advantages in biological activity, bone integration ability and long-term stability, providing a new solution for the development of orthopedic implants.
[0154] In order to comprehensively evaluate the effectiveness and superiority of the composite porous bioceramic metal prosthesis and the preparation method thereof of the present invention, a series of test experiments were designed to verify the core innovation of the present invention from multiple perspectives and to deeply explore its mechanism of action.
[0155] First, in vitro bioactivity evaluation was performed. The samples were immersed in simulated body fluid (SBF) to observe the formation of hydroxyapatite (HA) layer. The experimental conditions were as follows: the samples were immersed in SBF at 37°C, taken out after 7 and 14 days, and the surface morphology was observed by scanning electron microscopy (SEM), and the crystallinity of the HA layer was analyzed by X-ray diffraction (XRD).
[0156] Secondly, the mechanical properties of the samples were evaluated. Compression tests and interface shear strength tests were performed to examine the mechanical properties of the prosthesis and the bonding strength of the coating. The compression test was performed using a universal testing machine with a loading rate of 0.5 mm / min. The interface shear strength test was performed using the push-out method with a dedicated fixture and a loading rate of 0.5 mm / min.
[0157] Again, in vitro cell experiments were conducted to evaluate the biocompatibility of the samples. Human bone marrow mesenchymal stem cells (hBMSCs) were selected to observe the adhesion, proliferation and osteogenic differentiation of cells on the sample surface. The cells were cultured in an incubator at 37°C and 5% CO2. CCK-8 proliferation experiments were performed after 3 and 7 days, and alkaline phosphatase (ALP) activity was measured after 14 days.
[0158] Finally, the degradation behavior of the coating was evaluated by in vitro degradation experiments. The samples were immersed in phosphate buffered saline (PBS) at pH 7.4, incubated in a constant temperature oscillator at 37°C, and taken out after 7, 14, and 28 days, respectively, to measure the calcium ion concentration and pH value changes in the solution.
[0159] Table 1 shows the HA layer thickness and crystallinity index of all samples after immersion in SBF for 14 days:
[0160]
[0161]
[0162] Table 2 shows the compressive strength and interfacial shear strength of the samples:
[0163]
[0164] Table 3 shows the cell proliferation rate of hBMSCs after 7 days of culture on the sample surface and the ALP activity after 14 days:
[0165]
[0166]
[0167] Table 4 shows the calcium ion release and pH changes of the samples after immersion in PBS for 28 days:
[0168]
[0169]
[0170] Based on the above experimental results, the following conclusions can be drawn:
[0171] 1. Bioactivity: Examples 1-4 all showed excellent bioactivity and formed thicker and more crystalline HA layers. In particular, Example 3 showed the best HA layer formation ability, which may be attributed to its highest β-TCP content, providing more calcium and phosphorus ions to promote the deposition of HA.
[0172] 2. Mechanical properties: Example 2 exhibits the best comprehensive mechanical properties, which is due to its optimized gradient porous structure and coating composition. It is worth noting that although Comparative Example 1 has the highest compressive strength, the lack of bioceramic coating leads to a significant reduction in its biological activity.
[0173] 3. Biocompatibility: Example 3 exhibited the best cell proliferation and differentiation effects, which may be due to its optimal ratio of HA and β-TCP, providing an ideal microenvironment for cells. The cell compatibility of Comparative Example 1 was significantly poor, which once again demonstrated the importance of bioceramic coatings.
[0174] 4. Degradation behavior: Example 3 exhibits the most ideal degradation behavior, releasing an appropriate amount of calcium ions and maintaining a relatively stable pH environment. Comparative Example 4 degrades too quickly due to the excessively high β-TCP content, which may affect long-term stability.
[0175] Taking all factors into consideration, Example 3 can be regarded as the best example of the present invention, which has the best performance in terms of bioactivity, cell compatibility and degradation behavior, while maintaining good mechanical properties.
[0176] After in-depth analysis of these results, it is found that the present invention has the following unexpected technical effects:
[0177] 1. Synergistic effect: The combination of HA and β-TCP not only achieves the regulation of degradation rate, but also improves the overall biological activity. This synergistic effect may be due to the unique microenvironment formed by the two materials during the degradation process, which is conducive to the adhesion and proliferation of bone cells.
[0178] 2. Stress distribution optimization: The gradient porous structure not only improves the mechanical properties, but also optimizes the stress distribution. This structure may simulate the structural characteristics of natural bone tissue, help reduce the stress shielding effect, and promote the long-term reconstruction of bone tissue.
[0179] 3. Enhanced interface bonding: Micro-arc oxidation pretreatment not only improves coating adhesion, but also forms a functional gradient transition layer between the metal substrate and the ceramic coating. This transition layer may further optimize stress distribution and improve overall mechanical stability.
[0180] 4. Dynamic microenvironment regulation: As the coating slowly degrades, the released ions may continue to affect the surrounding microenvironment, forming a dynamically changing bioactive interface. This dynamic process may be closer to the metabolic process of natural bone tissue, which is conducive to long-term bone integration.
[0181] 5. Multi-scale synergistic effect: From nano-scale crystal structure to micro-scale pore structure, and then to macro-gradient design, the present invention achieves performance optimization at multiple scales. This multi-scale synergy may be the key to the superior comprehensive performance of the present invention.
[0182] In summary, the present invention achieves synergistic optimization of performance at multiple levels through a carefully designed material combination and preparation process, providing new ideas and directions for the development of orthopedic implants. These unexpected technical effects not only reflect the innovation of the present invention, but also provide valuable inspiration for the design of future bone tissue engineering materials.
[0183] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A metal prosthesis of a composite porous bioceramic, characterized in that: include: A metal substrate, wherein the metal substrate is made of Ti6Al4V alloy, has a gradient porosity structure of 30-70%, and a pore size range of 200-600 μm; The bioceramic coating is covered on the surface of the metal substrate and is composed of the following components in parts by weight: Hydroxyapatite HA 60-80 parts; β-tricalcium phosphate β-TCP 20-40 parts.
2. The composite porous bioceramic metal prosthesis according to claim 1, characterized in that: The composition of the Ti6Al4V alloy includes by weight percentage: Al5.5-6.5%, V3.5-4.5%, Fe≤0.25%, O≤0.13%, C≤0.08%, N≤0.05%, hydrogen H≤0.012%, and the balance is Ti, totaling 100%.
3. The method for preparing a composite porous bioceramic metal prosthesis according to claim 1, characterized in that: The following steps are involved: (1) Preparing porous Ti6Al4V matrix using selective laser melting (SLM) 3D printing technology; (2) performing surface treatment on the porous Ti6Al4V substrate; (3) Bioceramic coating on the surface treated porous Ti6Al4V substrate; (4) Heat treatment of the coated samples.
4. The preparation method according to claim 3, characterized in that: The process parameters of SLM 3D printing in step (1) are: Laser power is 150-250W, scanning speed is 600-1000mm / s, layer thickness is 30-50μm, spot diameter is 70-100μm, molding atmosphere is high-purity argon with purity ≥99.999%, molding chamber temperature is 80-120℃, and substrate preheating temperature is 150-200℃.
5. The preparation method according to claim 3, characterized in that: The surface treatment in step (2) comprises the following sub-steps: First, an acid etching treatment is performed, wherein the formula of the acid etching solution is HF (48 wt%): HNO3 (65 wt%): H2O = 1:4:5 (volume ratio), and the treatment is performed at 20-25° C. for 8-12 min, with a stirring speed of 200-300 rpm; Secondly, alkali treatment is performed, wherein the alkali solution is 5-10 mol / L NaOH solution, and the treatment is performed at 60-80° C. for 4-6 hours with a stirring speed of 100-150 rpm; Then, ultrasonic cleaning was performed with deionized water for 10-15 min at an ultrasonic frequency of 40-60 kHz; Finally, dry at 60-80°C for 2-4h.
6. The preparation method according to claim 3, characterized in that: The bioceramic coating in step (3) includes the following sub-steps: (a) MAO pretreatment by micro-arc oxidation; (b) Electrophoretic deposition (EPD).
7. The preparation method according to claim 6, characterized in that: The process parameters of the micro-arc oxidation MAO pretreatment are: The electrolyte formula is Ca(CH3COO)2·H2O10-15g / L, Na2HPO4·12H2O20-30g / L, voltage is 300-400V, frequency is 500-1000Hz, duty cycle is 10-20%, processing time is 5-10min, and temperature is 10-20℃.
8. The preparation method according to claim 6, characterized in that: The process parameters of the electrophoretic deposition EPD are: The suspension formula is 6-8g / L HA powder, 2-4g / L β-TCP powder, 0.1-0.3g / L dispersant, and the solvent is ethanol; The pH value is 4.0-5.0, the voltage is 60-80V, the deposition time is 3-5min, and the temperature is 20-25℃.
9. The preparation method according to claim 3, characterized in that: The process parameters of the heat treatment in step (4) are: The heating rate is 5-10°C / min, the heat treatment temperature is 800-1000°C, the holding time is 1-2h, and the furnace is used to cool to room temperature. The heat treatment atmosphere is high-purity argon with a purity of ≥99.999%.
10. The preparation method according to claim 8, characterized in that: The preparation method of the HA powder and the β-TCP powder comprises: For HA powder, 23.6-24.0 g Ca(NO3)2·4H2O and 7.9-8.1 g (NH4)2HPO4 were dissolved in deionized water, and the (NH4)2HPO4 solution was slowly added to the Ca(NO3)2 solution under continuous stirring. The pH was adjusted to 10-11 with NH4OH, and the mixture was stirred at 70-80°C for 4-6 h. After aging for 24 h, the mixture was filtered, washed, and dried, and finally calcined at 900-1000°C for 2 h. For β-TCP powder, 35.4-36.0 g Ca(NO3)2·4H2O and 15.8-16.2 g (NH4)2HPO4 were dissolved in deionized water, and the (NH4)2HPO4 solution was slowly added dropwise to the Ca(NO3)2 solution under continuous stirring, and the pH was adjusted to 7-8. The mixture was stirred at 80-90°C for 5-6 h, aged for 24 h, filtered, washed, and dried, and finally calcined at 900-1100°C for 3 h. The obtained powder was ball-milled and then passed through a 200-mesh sieve.
Citation Information
Patent Citations
Method for preparing titanium-base / silicon-substituted hydroxyapatite biological coating
CN101279108A
Highly active biological gradient coating for titanium alloy surface
CN103668397A
Surface hydroxyapatite coating of titanium alloy for joint prosthesis and preparation method thereof
CN110055573A
Preparation method of titanium implant with surface-controllable micro-nano composite structure biological membrane
CN112170841A
METHOD FOR PRODUCING A BIOLOGICALLY ACTIVE COATING
EA201101715A1